Neuropeptide TIP39 as a pluripotent brain molecule and its potential functions in postpartum depression - Wang, Silin; Liu, Hongchi; Tang, Qiuyi; Liao, Ning; Liu, Tianhao; Yang, Zhengzhong; Wei, Yanghui; Fu, Rao (Frontiers in Endocrinology, 2026)
BackgroundThe tuberoinfundibular peptide of 39 residues (TIP39) is a small peptide first extracted in 1997, which has garnered limited research attention. It belongs to the parathyroid hormone (PTH)–related peptides family and specifically binds the parathyroid receptor type 2 (PTH2R). It is gaining attention for its roles in mood regulation, maternal behavior, and social functions. Its potential in modulating these processes possibly positions TIP39 as an underexplored candidate for exploring complex physiological functions of postpartum depression.AimsGiven the accumulating evidence of TIP39’s involvement in various regulatory functions, this review aims to investigate its potential as a common pathway for postpartum depression PPD-related symptoms, including depressive mood and maternal behaviors. Specifically, the focus is on exploring the possibility of TIP39 as a key modulator in the pathophysiology of PPD, with the goal of identifying a new entry point for the treatment of this mental health disorder.ConclusionsThe multifunctional nature of TIP39, as evidenced by its roles in diverse physiological processes, opens up a promising avenue for further investigation. The investigation of TIP39’s role in mood regulation and maternal behavior provides a possible rationale for its consideration as a therapeutic target for PPD. This review is a tentative step to bridge TIP39 and PPD symptoms, with the ultimate goal of providing a new sight for the remedy of this prevalent and often debilitating disorder.